The Complete Jean Vigo - Vigo, Jean; Kaufman, Boris (Artificial Eye, 2004)
Although Vigo died at the age of 29, having made just four films - of which two are undisputed masterpieces - he is unquestionably one of the great masters of French cinema. This 2 disc set presents beautifully restored versions of the films and a fascinating array of supplementary features. [www.amazon.de]
Keywords: DVD-Video